Human papillomavirus vaccine in boys: background rates of potential adverse events. Issue 10 (3rd June 2013) - Clothier, Hazel J; Lee, Katherine J; Sundararajan, Vijaya; Buttery, Jim P; Crawford, Nigel W
Abstract: Objectives: To determine background rates of potential adverse events following immunisation (AEFI) before expansion of the quadrivalent human papillomavirus (4vHPV) vaccination program to adolescent boys. Design, patients and setting: Retrospective analysis of hospital discharge data obtained from the Victorian Admitted Episodes Dataset and emergency department visit data obtained from the Victorian Emergency Minimum Dataset for boys aged 12 to < 16 years during the period 1 July 2004 to 30 June 2009. Main outcome measures: Numbers of and incidence rates for Guillain‐Barré syndrome, anaphylaxis, seizures, syncope and other potential AEFI from 1 July 2004 to 30 June 2009, and estimated numbers of events after 4vHPV vaccination assuming no association (other than temporal) with the vaccine. Results: We estimated background rates of neurological and allergic events in adolescent boys to be 252.9 and 175.2 per 100 000 person‐years, respectively. Assuming an 80% vaccination rate with three doses per person — which equates to 1 440 000 doses administered nationally per year in the first 2 years of the program — about 2.4 episodes of Guillain‐Barré syndrome would be expected to occur in the 6 weeks following vaccination. Within 1 day of vaccination, about 3.9 seizures, 0.3 episodes of anaphylaxis and 6.5 acute allergy presentations would be expected. Conclusions: Routinely collected health outcome administration data can inform postlicensure safety surveillance of target conditions that might be perceived as AEFI.